A Jurassic pterosaur from Patagonia and the origin of the pterodactyloid neurocranium - Codorniú Dominguez, Laura Susana (2016)
Pterosaurs are an extinct group of highly modified flying reptiles that thrived during the Mesozoic. This group has unique and remarkable skeletal adaptations to powered flight, including pneumatic bones and an elongate digit IV supporting a wingmembrane. Two major body plans have traditionally been recognized: the primitive, primarily long-tailed paraphyletic "rhamphorhynchoids" (preferably currently recognized as non-pterodactyloids) and the derived short-tailed pterodactyloids. These two groups differ considerably in their general anatomy and also exhibit a remarkably different neuroanatomy and inferred head posture, which has been linked to different lifestyles and behaviours and improved flying capabilities in these reptiles. Pterosaur neuroanatomy, is known from just a few three-dimensionally preserved braincases of non-pterodactyloids (as Rhamphorhynchidae) and pterodactyloids, between which there is a large morphological gap. Here we report on a new Jurassic pterosaur from Argentina, Allkaruen koi gen. et sp. nov., remains of which include a superbly preserved, uncrushed braincase that sheds light on the origins of the highly derived neuroanatomy of pterodactyloids and their close relatives. A mCT ray-generated virtual endocast shows that the new pterosaur exhibits a mosaic of plesiomorphic and derived traits of the inner ear and neuroanatomy that fills an important gap between those of non-monofenestratan breviquartossans (Rhamphorhynchidae) and derived pterodactyloids. These results suggest that, while modularity may play an important role at one anatomical level, at a finer level the evolution of structures within a module may follow a mosaic pattern. Copyright 2016 Codorniú et al.